Prevalence of Depression among Stroke Survivors: Racial-Ethnic Differences - Fei, Kezhen (Stroke, 2015)
BACKGROUND AND PURPOSE: Although post-stroke depression is common, racial-ethnic disparities in depression among stroke survivors remain under-explored. Thus, we investigated the relationship between race/ethnicity and depression in a multi-racial-ethnic stroke cohort. METHODS: Baseline survey data of validated scales of depression and functional status, demographics, comorbidities and socioeconomic status were used from a recurrent stroke prevention study among community-dwelling urban stroke/TIA survivors. RESULTS: The cohort included 556 participants with a mean age of 64 years. The majorities were Black (44%) or Latino (42%), female (60%), had their last stroke/TIA nearly two years prior study enrollment, and lived below the poverty level (58%). Nearly one in two Latinos, one in four Blacks and one in eight Whites were depressed. Multivariate logistic regression showed that survivors who were younger, female, had three or more comorbid conditions, were functionally disabled from stroke, lacked emotional or social support, and who took antidepressants prior to study entry had higher risk of depression. Time since last stroke/TIA did not affect the chance of depression. After adjusting for all above risk factors, Latinos had three times the odds of depression (95% CI: 1.18 – 6.35) than Whites; Blacks and Whites had similar odds of depression. CONCLUSION: This study reveals that Latino stroke survivors have a significantly higher prevalence of depression compared to their non-Latino counterparts.